English Department Third-Year Students’ Perception toward Full Online Learning During the COVID-19 Pandemic at Universitas Negeri Padang - Agrefina Agrefina; Muhammad Al-Hafizh (Journal of English Language Teaching, 2022)
The spread of the COVID-19 virus in Indonesia has affected human life in various sectors, including education. The learning system from conventional classrooms to online learning brings various views or opinions from both teachers and students. This study aims to determine student perceptions of online learning that has been carried out during the COVID-19 pandemic. This research was conducted at the English Department of Universitas Negeri Padang on 33 third-year students in the July-December 2020 semester. 25 statements were used in this study to find out how students perceive online learning. The result of this study is that students have a neutral perception of online learning that is being carried out during the pandemic with an average score of 2.87. However, the students considered that some platforms were considered inappropriate because they needed a lot of data packages to access, and there were platforms that could not be used to collect the assigments that had been done.